2018
DOI: 10.1002/oby.22341
|View full text |Cite
|
Sign up to set email alerts
|

Gene Coexpression Networks in Whole Blood Implicate Multiple Interrelated Molecular Pathways in Obesity in People with Asthma

Abstract: Objective: Asthmatic children who develop obesity through adolescence have poorer disease outcomes compared to those that do not. We aimed to characterize the biology of childhood asthma complicated by adult obesity. Methods: Gene expression networks are powerful statistical tools for characterizing human disease that leverage the putative co-regulatory relationships of genes to infer relevant biological pathways. We performed weighted gene co-expression network analysis (WGCNA) of gene expression data in wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Although it was most widely accepted that obesity or its metabolic complications constitute a risk factor for asthma and asthma morbidity, epidemiological evidence is accumulating on the reverse causal association from asthma to subsequent obesity. In addition, a recent study has identified co-expression network modules related to incident obesity among asthmatic children [31], providing biological evidence on asthma preceding the development of obesity. Coinciding with two population-based studies conducted on US children [4,7], the present results demonstrated that asthmatic children were at significantly increased risk of overweight and obesity, extending the literature with evidence from a large sample of Chinese children.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was most widely accepted that obesity or its metabolic complications constitute a risk factor for asthma and asthma morbidity, epidemiological evidence is accumulating on the reverse causal association from asthma to subsequent obesity. In addition, a recent study has identified co-expression network modules related to incident obesity among asthmatic children [31], providing biological evidence on asthma preceding the development of obesity. Coinciding with two population-based studies conducted on US children [4,7], the present results demonstrated that asthmatic children were at significantly increased risk of overweight and obesity, extending the literature with evidence from a large sample of Chinese children.…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging regulatory relationships in system-level gene expression data can highlight biological pathways implicated in obesity and offer further insights into the biological function of these genetic variants. Recent studies have demonstrated that whole-blood transcriptome profiles are valid biological data for weight status and thus provide a more parsimonious method to investigate the functional genomics of obesity, wherein both genes and pathways are included 1215 . To this end, we generated and integrated gene expression data of venous blood samples and clinical data for 90 individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The publication year ranged from 2006 to 2021. Sixteen articles (33%) were from America and Canada,33–48 14 (29%) were from Europe,49–61 11 (23%) were from Asia,62–72 five (10%) were from Australia and New Zealand,73–77 one (2%) was from Africa78 and one (2%) was from South America 79. Asthma was diagnosed by a physician and confirmed by variable airflow obstruction (airway hyper-responsiveness and/or bronchodilator reversibility) in 25 (52%) articles, physician-diagnosed in 19 (40%) articles, diagnosed as coded in a database in one (2%) article, and the method of asthma diagnosis was not reported in three (6%) articles.…”
Section: Resultsmentioning
confidence: 99%